2022
DOI: 10.1038/s41467-022-31324-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulating mitofusins to control mitochondrial function and signaling

Abstract: Mitofusins reside on the outer mitochondrial membrane and regulate mitochondrial fusion, a physiological process that impacts diverse cellular processes. Mitofusins are activated by conformational changes and subsequently oligomerize to enable mitochondrial fusion. Here, we identify small molecules that directly increase or inhibit mitofusins activity by modulating mitofusin conformations and oligomerization. We use these small molecules to better understand the role of mitofusins activity in mitochondrial fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Competing peptide MP1 and small molecules that mimic MP1 critical peptide side chains ( Rocha et al, 2018 ) promote MFN extended or unfolded conformations, thereby evoking mitochondrial fusion and motility. This mechanism of action has been independently validated for the commercially available compound “MASM7” ( Zacharioudakis et al, 2022 ), which was renamed from, but is chemically identical to, previously described Chimera parent compound “B01” ( Rocha et al, 2018 ). Importantly, each of the mitofusin activators employed herein exhibits identical fusogenic activity for MFN1 and MFN2 (i.e., in Mfn2 null and Mfn1 null cells, respectively), and lacks fusogenic activity in cells lacking mitofusins (i.e., Mfn1/Mfn2 double null cells) ( Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Competing peptide MP1 and small molecules that mimic MP1 critical peptide side chains ( Rocha et al, 2018 ) promote MFN extended or unfolded conformations, thereby evoking mitochondrial fusion and motility. This mechanism of action has been independently validated for the commercially available compound “MASM7” ( Zacharioudakis et al, 2022 ), which was renamed from, but is chemically identical to, previously described Chimera parent compound “B01” ( Rocha et al, 2018 ). Importantly, each of the mitofusin activators employed herein exhibits identical fusogenic activity for MFN1 and MFN2 (i.e., in Mfn2 null and Mfn1 null cells, respectively), and lacks fusogenic activity in cells lacking mitofusins (i.e., Mfn1/Mfn2 double null cells) ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The recent development of small molecule mitofusin activators made it possible to investigate mitofusin functioning without experimentally perturbing Mfn1 or Mfn2 levels. To date, three chemical classes of mitofusin activators have been described: triazolureas ( Rocha et al, 2018 ; Zacharioudakis et al, 2022 ), phenylhexanamides ( Dang et al, 2020, 2021 ), and derivatives of the natural compound piperine ( Zhang et al, 2022 ). All of these small molecule mitofusin activators chemically mimic amino acid side chains that determine mitofusin protein conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that MFN1-specific agonist leflunomide enhanced IFN1 production. Leflunomide is also known as an anti-inflammatory drug used against rheumatoid arthritis, which increases mitochondrial elongation by depleting the pyrimidine pool and altering MFN1/2 protein levels through loss of pyrimidine synthesis ( 19 , 29 ). In addition, with the consequence of MFN1 knockdown put into consideration, MFN1 might be a pharmacological target in the treatment of HCMV.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we use the Raft-Seq platform to examine neurologically relevant mutations in the MFN2 gene, which normally protects against cellular stress from damaged mitochondria by regulating mitochondrial fission and fusion 31 . Clinical MFN2 mutations (pathogenic variants) primarily result in Charcot-Marie-Tooth Disease, the most common inherited neuromuscular disorder characterized by peripheral neuropathy with impairment of the central nervous system 32 36 . We find that the phenotype caused by pathogenic MFN2 variants is distinct, but the difference is not adequately described by a single measurement/feature, necessitating a more complex feature analysis.…”
Section: Introductionmentioning
confidence: 99%